Analisis Kepatuhan Jaga Jarak Fisik untuk Mencegah Penyebaran Covid-19 di Indonesia: Scoping Review - M. Karomah Nastiti Melania; Inge Dhamanti (Media Gizi Kesmas, 2023)
Background: Obedience is a positive attitude shown by someone in response to a regulation. Physical distancing is one of the ways to limit physical contact to stop the spread of infectious diseases such as Covid-19. Keeping a distance from other people when in a crowd is important to apply. Because wearing a mask is not enough to prevent someone from being exposed to other people's droplets. Physical distancing can also prevent the transmission of Covid-19 from people who are not aware that they have been infected and are not self-isolating. Objectives: This study aim to determine physical distancing obedience in a group of people who live throughout Indonesia. Methods: This study was scoping review research.  Article searches were conducted through Google Scholar anf Portal Garuda.. The keywords used to search for articles included "masyarakat” AND "jarak fisik” OR "jaga jarak” "OR "kepatuhan” AND "Covid-19" dan "community” AND "physical distancing” OR "social distancing” OR "obedience” AND "Covid-19”. Results: The results of the search for articles found were 30 articles and 6 articles were taken to be analyzed because they met the research inclusion criteria. From several articles analyzed, the result show that in West Nusa Tenggara the level of obedience with physical distancing has not reached half of the people studied. In Ubud, Bali, it was shown that the majority of people implemented physical distancing but did not meet the standard of more than 1 meter. The people of the Riau, DKI Jakarta, Sumerta Kelod, and 16 other provinces show that community obedience with physical distancing is quite good. Conclusions: The conclusion that can be drawn is that the obedience amongs Indonesian people are  fairly good category regarding physical distancing, even though there are differences in the level of compliance in several regions.